Risk factors of ventilator-associated pneumonia in neonates after cardiac surgery with cardiopulmonary bypass - Khemio Arnes, S.; Zgrzheblovska, L.; Moshkivska, L.; Boyko, S.; Perepeka, I.; Truba, Y.; Lazoryshynetz, V. (Ukrainian Journal of Cardiovascular Surgery, 2017)
Objective: identify the risk factors of ventilator-associated pneumonias in newborns after cardiac surgery with cardiopulmonary bypass. Methods: 39 patients of neonatal age with congenital heart diseases who underwent cardiac surgery and who were on mechanical ventilation for more than 24 hours in the postoperative period were included in this study. Results: during this investigation 39 patients were examined. The strains of microorganisms that most often cause ventilator-associated pneumonia in newborns have been found: Pseudomonas aeruginosa, Klebsiella pneumoniae, Enterococcus faecalis. Patients who are on artificial ventilation for more than 72 hours, and those who undergo surgery with a high level of complexity, are more likely to develop pneumonia. Conclusions: Newborns after cardiac surgery with cardiopulmonary bypass with ventilator-associated pneumonia have a longer stay in the intensive care unit.